Determination of Content Marketing and Store Atmosphere on Café Consumer Responses - Kuraesin, Ecin; Nugrahanigsih, Hartanti; Agung, Syahrum; Dwi Tresnawati, Evita; Hikmat Maulana, Lucky (Publisher Cv. Inara, 2024)
The development of the culinary business is increasingly rapid, marked by the emergence of many cafes which are increasingly common in Indonesia. Many cafes run culinary businesses that take advantage of practicality in consuming food and drinks. This research aims to determine consumer responses and the influence of content marketing and store atmosphere factors on consumer responses to café visitors simultaneously or partially. The population and sample are 120 consumers taken by nonprobability sampling technique. The analytical method used in this research is descriptive and verification. The instrument test was carried out with validity and reliability. Research data analysis includes multiple linear regression analysis, multiple correlation analysis, and hypothesis testing. The research results show that content marketing and store atmosphere are considered good. Simultaneously and partially, content marketing and store atmosphere factors have a positive and significant effect on consumer responses.